2022
DOI: 10.3389/fpubh.2022.849093
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mental Health, Well-Being and Active Lifestyles of University Students by Means of Physical Activity and Exercise Research Programs

Abstract: Mental disorders (e.g., depression) and sedentary behavior are increasing, also among emerging adults. One particular target group of emerging adults with high sitting times and vulnerability to mental disorders are university students. In particular, anxiety and depressive symptoms as well as stress symptoms are very common among university students. The present manuscript discusses whether physical activity and exercise interventions can help to promote the mental health of emerging adults such as university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 61 publications
4
27
0
Order By: Relevance
“…The adoption of such a closed management policy may lead to higher levels of depression, anxiety, and stress and lower levels of subjective wellbeing among school students (43). In this context, this study found that students' MPA was negatively associated with depressive symptoms, this result could be supported by previous studies conducted by Herbert among university students after a few weeks of intervention (44). and the role of moderate-to-vigorous physical activity (MVPA) in alleviating depressive symptoms has also been widely recognized (45)(46)(47).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The adoption of such a closed management policy may lead to higher levels of depression, anxiety, and stress and lower levels of subjective wellbeing among school students (43). In this context, this study found that students' MPA was negatively associated with depressive symptoms, this result could be supported by previous studies conducted by Herbert among university students after a few weeks of intervention (44). and the role of moderate-to-vigorous physical activity (MVPA) in alleviating depressive symptoms has also been widely recognized (45)(46)(47).…”
Section: Discussionsupporting
confidence: 83%
“…The adoption of such a closed management policy may lead to higher levels of depression, anxiety, and stress and lower levels of subjective wellbeing among school students ( 43 ). In this context, this study found that students' MPA was negatively associated with depressive symptoms, this result could be supported by previous studies conducted by Herbert which validated the effectiveness of exercise in preventing and reducing depressive symptoms at university students populations, that exercise interventions comprising aerobic exercises of low- to moderate intensity may work best to improve mental health among university students after a few weeks of intervention ( 44 ). and the role of moderate-to-vigorous physical activity (MVPA) in alleviating depressive symptoms has also been widely recognized ( 45 47 ).…”
Section: Discussionsupporting
confidence: 82%
“…The existing research has generally discussed the relationship between physical exercise and mental health. For example, studies based on adolescents have found that physical exercise can alleviate depression caused by interpersonal problems ( 25 ), and higher levels of exercise have a positive effect on mental health ( 19 , 26 ). At the same time, other studies have found that exercises help to reduce the frequency of smoking and develop a lifestyle conducive to both physical and mental health ( 15 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…At the same time, compared with previous studies that support the positive effects of exercises ( 19 , 25 , 26 , 28 , 29 ), we further systematically examine the heterogeneities in physical activity's benefits among different subgroups. Heterogeneity analysis shows that there is no significant gender difference in the health benefits of physical exercise, but its impact is more prominent for people with mental disorders who are younger and higher educated, with better health status, and live in urban areas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation